The first case of IgG4-related disease in Italy - Davide Rolla; Diego Bellino; Giancarlo Peloso; Maria Pia Rastaldi; Paola Simonini; Jean Louis Ravetti (Society of Diabetic Nephropathy Prevention, 2013)
Background: Recently, Mikulicz's disease has been defined as an IgG-4 related disease, a systemic condition, where the hallmark pathology findings are lymphoplasmacytic infiltrates, immunoglobulin (Ig)G4-positive plasma cells, modest tissue eosinophilia, and intense fibrosis. Case: We present a case of 63-year-old man who showed epigastralgia and elevated serum lipase levels. Computed tomography of the abdomen revealed a bulky mass of the pancreas, so he underwent bilious-digestive anastomosis, and biopsy of the pancreas revealed massive infiltration of lymphocytes and plasma cells. The patient was therefore diagnosed with sclerosing chronic pancreatitis (Kuttner's tumour). After one year, the patient began to exhibit signs of "sicca syndrome", and at the same time, he demonstrated progressive renal failure. Immunological tests showed hypocomplementemia, and the renal biopsy specimen demonstrated interstitial inflammation, in which infiltrate was composed of lymphocytes, while infiltrating plasma cells showed immunoreactivity to IgG4. Sialography revealed severe involvement of the salivary glands, and Schirmer's test resulted positive. Conclusions: Here, we report successful treatment of the first case in Italy of a patient with hypocomplementemic tubulointerstitial nephritis in IgG4-related disease.